Diversidad de Orquídeas en el “Parque Nacional Iztaccíhuatl-Popocatépetl” (México) y sus áreas de influencia - Luna-Rosales, Bárbara (Universidad de Costa Rica, 2015)
Iztaccíhuatl and Popocatépetl National Park is 25,679 ha in size and it comprises the Transmexican Neo-volcanic strip. The floristic wealth of the Park approximately represents 4% of the flora of the country and the Orchidaceae is one of the families of this flora. Mexico has 1400 orchid species including in 159 genera; the importance at a world-wide level of this flora increases when around 900 species exist only in Mexico. In 1996, 25 orchid species were reported for the Park without a field register. These species and their populations can drastically have varied and in some cases disappeared due to the alterations of the habi- tat and to the extraction of the plants of the last decades. In June of 2001 we started the present project which the main objective has been to obtain by means of work in field, the updated listing of the orchid flora of this Park at different seasons of the year, as well as to determine the diversity of species, plant development stage, their altitudinal distribution and abundance. After 5 years of work 39 species have been located, 25 species are new registers to the Park and there were confirm only 14 species of the 1996 listing.